Mergers & acquisitions integration handbook : helping companies realize the full value of acquisitions - Whitaker, Scott C., 1963- (Hoboken, NJ : John Wiley & Sons, 2012)
Proven strategies and tactics to manage the integration of acquired and/or merged companies Mergers & Acquisitions Integration Handbook is a comprehensive resource to help companies create a scalable post merger or acquisition integration process and framework that accelerates operating and business benefit goal realization. Includes tools, templates, forms, examples and checklists to provide a no nonsense "handbook" style approach to managing an effective integration. Helps integration managers quickly get up to speed on various integration challenges, including guidance on developing detailed.
Mergers & Acquisitions Integration Handbook: Helping Companies Realize the Full Value of Acquisitions; Contents; Acknowledgments; CHAPTER 1 Introduction; WHO SHOULD USE THIS BOOK?; HOW THIS BOOK IS SET UP; CHAPTER SUMMARIES; A WORD TO THE WISE; CHAPTER 2 Mergers and Acquisitions 101 and Assessing Integration Complexity and Risk; MERGERS AND ACQUISITIONS 101; DETERMINING POST-ACQUISITION INTEGRATION SCOPE; Subsidiary Bolt-on Acquisition; Functional Integration; Functional, Operational, and Full Integrations; ASSESSING INTEGRATION COMPLEXITY AND RISK; Due Diligence.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Consolidation and merger of corporations; BUSINESS & ECONOMICS / Mergers & Acquisitions; Consolidation and merger of corporations; BUSINESS & ECONOMICS / Mergers & Acquisitions; Consolidation and merger of corporations; Electronic books; Electronic books; Electronic books